The Impacts of Public Libraries in Promoting Knowledge Society among Civil Servants in Nigeria - K. T. Omopupa; Hadi Ayodeji Abdul; Kabir Alabi Sulaiman; Olamide Easther Olajide (Insaniyat : Journal of Islam and Humanities, 2022)
Public libraries serve as gateways to knowledge and culture by playing a fundamental role in society. The aim of this study is to examine the impacts of public libraries on the promotion of knowledge societies among civil servants in Oyo State, Nigeria. The total population was 570, and the sample size was 235 using a simple random sampling technique. The research design adopted was a descriptive survey. A questionnaire was used as an instrument for data collection, and a descriptive data analysis technique of frequency and the simple percentage was used. Findings revealed, firstly, that public libraries promote knowledge societies among civil servants through their collections, resources, and internet facilities to enhance the civil service culture. Secondly, public libraries have contributed significantly to improving and promoting knowledge societies as the civil servants make judicious use of the library facility to promote knowledge societies. Thirdly, public libraries have limitation that hindered the promotion of knowledge societies among civil servants; which are inadequate library materials, poor reading culture, inaccessibility to information resources, poor dissemination of information, and inadequate professional staff have. The recommendations of this study are the public libraries should provide more collections, adequate information resources tailored toward the promotion of knowledge societies, recruit professional staff and conduct regular training to improve their discharge of duties to meet the information needs of civil servants for the promotion of knowledge societies.